Serum Antioxidant Status in Sickle Cell Disease Patients: Implications for Oxidative Stress and Disease Severity - Ali Hadi, Zainab; Al-Tu’ma, Fadhil Jawad; Hameid Odda, Atheer; Almuhafdah, Hawra (Journal of Contemporary Medical Sciences, 2023)
Objectives: The main aim of this subject is to determine the oxidative status of Iraqi sickle cell anemic patients and then correlated with various biomarkers. Methods: In this study, blood samples from 100 sickle cell anemic subjects were analyzed, and then compared with control group which consisting of 50 individuals without sickle cell anemia was established. Various biochemical techniques were employed to measure different oxidative stress markers and inflammatory mediators. Serum samples were collected from blood to determine the levels of antioxidants such as catalase (CAT), glutathione peroxidase (G-Px), reduced glutathione (GSH), and lipid-peroxidation product malondialdehyde (MDA). Results: The results revealed that the levels of serum antioxidant activity (CAT), GSH, and G-Px were significantly reduced with (P < 0.05) in sickle cell anemic patients as compared with apparently control group. In contrast, the MDA level was significantly higher in sickle cell anemic patients than that found in the apparently control group. Conclusion: In this work, there is an increased oxidative stress in sickle cell anemic patients, which is accompanied by a decrease in antioxidant activity and a rise in lipid peroxidation, leading to the intensification of sickle cell anemic symptoms in patients.